2007
DOI: 10.1063/1.2432270
|View full text |Cite
|
Sign up to set email alerts
|

Superradiant terahertz Smith-Purcell radiation from surface plasmon excited by counterstreaming electron beams

Abstract: The authors show that evanescent tunneling transmission of effective surface plasmon polaritons between two counterstreaming electron beams noticeably increases Smith-Purcell radiation (SPR) intensity by about two orders of magnitude as well as lower its transition threshold from a spontaneous emission to a stimulated one. An emission mechanism of the superradiant SPR is theoretically analyzed by the dielectric conversion of the structured metal surface and the boundary matching condition of Maxwell’s equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 15 publications
2
38
0
Order By: Relevance
“…This device is abstractly shown in Fig. 9.1 and is frequently studied in electron-beam driven frequency multiplication processes [17] and certainly it is a promising candidate for producing terahertz radiation [7,[18][19][20]. As discussed in the most of theoretical studies [19] and in experimental ones [21], SPR power is still very low which its origin seems to be from its spontaneous nature.…”
Section: Introductionmentioning
confidence: 97%
“…This device is abstractly shown in Fig. 9.1 and is frequently studied in electron-beam driven frequency multiplication processes [17] and certainly it is a promising candidate for producing terahertz radiation [7,[18][19][20]. As discussed in the most of theoretical studies [19] and in experimental ones [21], SPR power is still very low which its origin seems to be from its spontaneous nature.…”
Section: Introductionmentioning
confidence: 97%
“…of 50-500 A/cm 2 over the beam cross section is one of the crucial requirements [5][6][7][8]. The previously proposed works mainly adopt two approaches for creating the sheet-beam: (1) direct approach, developing a sheet-beam gun that produces sheet-beam via beam compression in vertical direction using various beam focusing electrodes (BFE) for different cathode shapes [9][10][11], and (2) indirect approach, using a conventional spherical cathode followed by a solenoid lens system to transform circular beam to elliptical beam [12,13], such system would significantly increase the total length of the gun.…”
mentioning
confidence: 99%
“…In recent experiments [6]− [8], it has been shown that the SP radiation provide a promising candidate to realize compact and tunable radiation source in the THz region. FELs based on the SP effect are operated in the amplifier and oscillator configurations where the optical feedback is required in the latter case [9][14]. Such FELs could be made with much more compact device structure compared to other FELs (e.g., undulator FELs), and therefore may be interesting for application.…”
Section: Introductionmentioning
confidence: 99%